Odločanje o varstvu in vzgoji otrok - Rijavec, Vesna (Pravni letopis, 2019)
Act on non-contentious procedure, with the new procedural rules of family matters, completes the regulation of Family Code. The paper only deals with the proceedings on care and education of children. The regulation of this part of parental care is presented by the main procedural institutes and fundamental principles, taking into account specific procedural solutions tailored to the specific nature of the procedure and the protection of the child`s benefits. As a rule, these proceedings are initiated on the motion of the eligible participant, but the court has a number of official powers, not only to conduct the procedure, but also to collect the facts in official manner. The position of the child and Centre of Social Work is further defined below. The course of the proceeding is also addressed by the analysis of personalized procedural actions such as settlement, decisions and remedies.
Keywords: best child`s interest; care and education of children; družinska vzgoja; Družinski zakonik; družinsko pravo; Family Code; joint custody; non-contentious civil procedure; otroci; participant; starševstvo; zakonodaja